2002
DOI: 10.2460/ajvr.2002.63.1053
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and urine electrolyte and mineral concentrations in Thoroughbred horses with recurrent exertional rhabdomyolysis after consumption of diets varying in cation-anion balance

Abstract: In clinically normal horses and in horses with RER, the DCAB strongly affects plasma and urine pH and the FE of sodium, potassium, chloride, and phosphorus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 39 publications
2
22
0
1
Order By: Relevance
“…The effect of acidification on mineral metabolism, especially renal excretion of major minerals as described in the present study in rabbits, has been demonstrated in other monogastric species before (Jaffe et al., ; Sartorius et al., ; Langendorf and Lang, ; Burnell, ; Kraut et al., ; Ching et al., ; Cooper et al., ; Riond, ; McKenzie et al., ; Topliff, ; Chen and Shan, ). As shown in Fig.…”
Section: Discussionsupporting
confidence: 80%
“…The effect of acidification on mineral metabolism, especially renal excretion of major minerals as described in the present study in rabbits, has been demonstrated in other monogastric species before (Jaffe et al., ; Sartorius et al., ; Langendorf and Lang, ; Burnell, ; Kraut et al., ; Ching et al., ; Cooper et al., ; Riond, ; McKenzie et al., ; Topliff, ; Chen and Shan, ). As shown in Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Our finding that hyperchloremia directly increased plasma c Ca 2+ , independent to its effect on pH as demonstrated by in vitro equivolume dilution and multivariate analysis of in vivo data, was consistent with the results of a study in cows in which IV administration of CaCl 2 resulted in higher ionized plasma Ca concentrations than when the same amount of calcium (20 mg/kg body weight) was administered as a calcium gluconate formulation . An increase in c Ca 2+ has been reported in studies where acidogenic rations were fed to sheep, cattle, and horses . In these studies, a diet‐induced increase in serum c Cl was associated with an increase in c Ca 2+ .…”
Section: Discussionmentioning
confidence: 81%
“…Such abnormalities (e.g., low or high FE Na values, raised FE PO 4 ) have been found in some horses and ponies suffering from musculoskeletal problems, in particular the equine rhabdomyolysis syndrome (Harris & Colles 1988, Harris & Snow 1991. It should be noted that no differences in electrolyte status as determined by the FE test was found between thoroughbred horses confirmed to have the intrinsic muscle defect (RER) and control horses (McKenzie et al 2002). It should be noted that no differences in electrolyte status as determined by the FE test was found between thoroughbred horses confirmed to have the intrinsic muscle defect (RER) and control horses (McKenzie et al 2002).…”
Section: Electrolyte Imbalancesmentioning
confidence: 96%
“…Whilst an electrolyte imbalance within the diet may be identified through dietary analysis, an issue within an individual animal may be difficult to determine accurately, One practical way may be to measure urinary fractional excretion (FE) of electrolytes (Harris & Colles 1988, Harris & Gray 1992, McKenzie et al 2002, 2003a, although this at best is only a guide because marked variation can occur due to differences in the core diet, effect of exercise, sampling technique and between individuals as well as within individuals from day to day. Averaging the results of freely voided urine taken on three consecutive days under the same conditions, at the same time of day (pre-exercise and before or >8 h after a concentrate meal, at least 2 weeks after an episode, having been fed a standard ration thought to provide adequate and balanced intake of electrolytes for at least 2 weeks) may increase accuracy.…”
Section: Electrolyte Imbalancesmentioning
confidence: 99%